Roman Africa : archaeological walks in Algeria and Tunis / by Gaston Boissier ; authorized English version by Arabella Ward. - Boissier, Gaston, 1823-1908. (Tufts University. Tisch Library., 2016)
1 online resource (xv, 344 pages, 4 unnumbered leaves of plates) : maps, plans.; "With four maps."; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.